ECO-INNOVATION, OWNERSHIP STRUCTURE AND FIRM OPERATIONAL PERFORMANCE: A STUDY ON MALAYSIAN OIL AND GAS COMPANIES - MUNODAWAFA, RUSSELL TATENDA (2020)

(untitled)
The main objective of this study is to investigate the relationship between ecoinnovation and firm operational performance.